Gospodarsko razstavišče - Slivnik, Lara (AR. Arhitektura, raziskave, 2006)
The article summarises part of the research titled The Buildings of Slovene Fairgrounds; architecture and structure, which dealt with the buildings in the six Slovene, fairgrounds from the architectural and structural aspects. The article presents the Fairground in Ljubljana: the site, some more important urbanistic solutions and the architectural and structural features of particular buildings. Th influence of contemporary global architectural and structural achievements is emphasised. The Ljubljana Fairground is an example of modern functionalist architecture. One of the fundamental theoretical starting points of functionalism was that the main elements of architectural expression are the structure and the load-hearing framework or building's skeleton. Special attention is given to achievements in the field of development of mushroom slab structures in Slovenia and worldwide.
Keywords: slovenska arhitektura; razstavišča; Exhibition and Convention Centre, Ljubljana; Gospodarsko razstavišče; funkcionalizem; Ljubljana